Factors affecting students' attitude toward online shopping - Delafrooz, Narges; Paim, Laily; Haron, Sharifah Azizah; Md. Sidin, Samsinar; Khatibi, Ali (Academic Journals, 2009)
To ensure the success of online business, it is important for the retailers to understand their targeted customers. The aim of this study examines the significance of attitude toward online shopping. The objectives of the study are two fold. The first section seeks to determine relationship between attitude towards online shopping with shopping orientations and perceived benefits scales. The second section investigates factors that influence peoples’ attitudes towards online shopping. A five-level Likert scale was used to determine students’ attitudes towards online shopping. A self-administered questionnaire, based on prior literature, was developed and a total of 370 post graduate students were selected by random sampling. The regression analysis demonstrated the determinants of consumers’ attitudes towards online shopping. Additionally, utilitarian orientations, convenience, price, wider selection influenced consumers’ attitudes towards online shopping.